Risk communication in health: theoretical and methodological aspects for the control of sanitary public emergencies - Liliana Gómez Castro (Centro Provincial de Información de Ciencias Médicas, 2017)
In the last decades the contemporary societies have been exposed in a recurrent way to situations of sanitary emergency, reason why the communication has become an important component of risk control.  In this work, the experiences of some authors and organizations in the management when facing sanitary emergencies and in the strategy of risk communication as fundamental tool are supported from the theoretical referent of risk communication; it is also emphasized in the necessity of risk communication as a systematic practice directed to face situations of sanitary public emergency, where the increase of risk perception  in the population will allow to minimize the negative effects of these events.